Empirically Examining Barriers to E‐business Adoption in SMEs in Indonesia. Issue 1 (5th December 2017) - Irma, Janita; Chong, Tristan; Ram, Jiwat
Abstract: We examine SMEs' attitudes towards e‐Business adoption from a multi‐dimensional perspective to provide an understanding of the challenges and barriers to e‐Business adoption in the SMEs context. We derive a framework containing the interaction among various elements that influence e‐Business adoption. The framework was analysed with data from case studies involving Indonesian SMEs. Prior findings have shown the importance of e‐Business for companies' growth. However, we have extended this evidence by providing an understanding of issues that are important for e‐Business adoption in the SMEs context. We have empirically established that e‐Business adoption occurs through an interaction of various internal and external factors with owner‐manager‐related factors having the greatest influence on the outcome. The understanding of issues identified by this study will help policy makers, business owners, industry institutions, and other stakeholders to influence the uptake of e‐Business among SMEs in Indonesia and elsewhere. Theoretical and practical implications are discussed.